Development of a Tool for Measuring and Analyzing Computer User Satisfaction - Bailey, James E.; Pearson, Sammy W. (Management Science, 1983)
This paper reports on a technique for measuring and analyzing computer user satisfaction. Starting with the literature and using the critical incident interview technique, 39 factors affecting satisfaction were identified. Adapting the semantic differential scaling technique, a questionnaire for measuring satisfaction was then created. Finally, the instrument was pilot tested to prove its validity and reliability. The results of this effort and suggested uses of the questionnaire are reported here.